Economics, today and tomorrow - Miller, Roger LeRoy (Mission Hills, Calif : Glencoe/McGraw-Hill, 1991)
Applies traditional economic theory to contemporary problems such as unemployment, inflation, and conflicting economic systems.
Keywords: Economics -- Juvenile literature; Consumer protection -- Juvenile literature; Economics; Consumer protection; United States -- Economic conditions -- 1971-1981 -- Juvenile literature